Bimetallic silver-gold nanoparticles decorated reduced graphene oxide for non-enzymatic glucose detection - Ali, Nur Atikah (2020)
This research has employed a chemical reduction method in one pot reaction to obtained a bimetallic silver-gold nanoparticles with varying volume ratio (4:0 to 0:4) decorated reduced graphene oxide for non-enzymatic glucose detection. The morphological observation and other physicochemical properties were characterized using Raman Spectra, Ultra Violet Visible Spectra, X-Ray Powder Diffraction, and High Resolution Transmission Electron Microscopy, respectively. Raman spectra analysis confirms the formation of GO and rGO. 3 reported band (D, G and 2D band) was observed in the region of 1350- 2713 cm-1 in all spectra, in which these band was used to interpreted disorder degree on intensity ratio of GO and rGO. UV-Visible spectra authenticated that, after GO was reduced to rGO, the absorption peak indicated there is an increase in electronic conjugation in the rGO hence suggesting the sp2 hybridization in carbon network are restored. The colour changes from brown to black dispersion of GO to rGO was another proof of successfully reduction of GO to rGO. UV-Visible spectra of bimetallic silver-gold nanoparticles with varying volume ratio (4:0 to 0:4) decorated reduced graphene oxide, exhibited only one absorption peak and the maximum absorption peak red-shifted from 420 nm to 535 nm in wavelength, with increasing of gold ratio in Ag:Au (1:3), hence revealing the formation of an alloy structure, respectively. X-ray diffraction analysis suggested the formation of crystalline silver and gold nanoparticles at reduced graphene oxide surface, due to the characteristic peaks obtained for both metal have a same standard bragg reflection values. The surface morphology revealed that, GO and rGO both have a wrinkle morphology; meanwhile bimetallic silver-gold nanoparticles with varying volume ratio (4:0 to 0:4) were successfully decorated on the surface of reduced graphene oxide in the particle size ranges of 20 nm to 55 nm. These variations of the size obtained for the nanoparticles are strongly dependent on the concentration used of two metal between silver and gold. Finally, a non-enzymatic glucose sensor based on indium tin oxide glass electrode was successfully modified with bimetallic silver-gold nanoparticles decorated reduced graphene oxide with varying the volume ratio in the range 4:0 to 0:4. Cylic voltammetry studies on the modified electrode showed that combination of bimetallic silver-gold nanoparticles exhibited a great electrochemical activities toward glucose oxidation compared to monometallic silver and gold nanoparticles. However, among of the bimetallic silver-gold nanoparticles at 3:1,1:1 and 1:3, it was found that, when the Ag:Au at 1:3 ratio, the modified electrode give a remarkable increase in peak current density, followed by Ag:Au at 1:1 and 3:1 ratio. A chronoamperometry was conducted to study the peak current dependent of the modified electrodes on the glucose concentration, and the current response was found to increase linearly along with the glucose concentration increment from 0-18mM. The results obtained also revealed that, the amperometry response of the modified electrodes with combination of bimetallic silver-gold nanoparticles give a higher value of current response compared to monometallic silver and gold nanoparticles. In addition, these finding strongly indicated that the composition and the average particles size between silver and gold nanoparticles in bimetallic system plays a significant role in determining the electrochemical oxidation of glucose. Among of all modified electrodes, S4 electrode with Ag:Au at 1:3 ratio, the current response were magnify to 765.57 μA mM cm-2 and low detection limit of 1.3 μM at signal to noise ratio (S/N = 3). Hence, we may concluded this S4 electrode may serve as an ideal candidate to develop an enzymeless, fast and responsive for future glucose biosensors application.